Pembinaan Pendidikan Agama Islam untuk Lanjut Usia - Zunaida, Laily; Sahrandi, Akhmad (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2021)
The development of Islamic religious education is very important for the elderly, because at an age that is no longer young, the elderly experience a lot of decline in their health both physically and mentally which causes their souls to shake. This situation can only be handled through the development of Islamic religious education. However, the elderly need spiritual guidance so that their old age becomes more meaningful. The development of Islamic religious education is also very much needed by the elderly to improve the quality of worship in the face of death, because by carrying out daily worship the elderly will increasingly remember Allah SWT.